2014
DOI: 10.1073/pnas.1311254111
|View full text |Cite
|
Sign up to set email alerts
|

Leucophores are similar to xanthophores in their specification and differentiation processes in medaka

Abstract: Animal body color is generated primarily by neural crest-derived pigment cells in the skin. Mammals and birds have only melanocytes on the surface of their bodies; however, fish have a variety of pigment cell types or chromatophores, including melanophores, xanthophores, and iridophores. The medaka has a unique chromatophore type called the leucophore. The genetic basis of chromatophore diversity remains poorly understood. Here, we report that three loci in medaka, namely, leucophore free (lf), lf-2, and white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
139
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(146 citation statements)
references
References 61 publications
7
139
0
Order By: Relevance
“…Leucophoroma was not reported earlier in fish. But the leucophoroma lesions observed in this study were compatible with those described by Deravi et al (2014) and Kimura et al (2014), who confirmed that spindloid cells contain light reflectile golden-yellow colour pigment granules.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Leucophoroma was not reported earlier in fish. But the leucophoroma lesions observed in this study were compatible with those described by Deravi et al (2014) and Kimura et al (2014), who confirmed that spindloid cells contain light reflectile golden-yellow colour pigment granules.…”
Section: Discussionsupporting
confidence: 92%
“…() and Kimura et al. (), who confirmed that spindloid cells contain light reflectile golden‐yellow colour pigment granules.…”
Section: Discussionmentioning
confidence: 85%
“…These genes showed a pattern of up-regulation due to hybridization and also further up-regulation effected by UVB exposure. Among these 18 genes, 4 genes are related to melanin synthesis ( mitfa , tyr , tyrp1a , dct ), 3 genes are related to melanosome transport ( rab27 , rab38a , pmela ), 4 genes are related to pigmentation ( slc2a11b , slc24a5 , oca2, pax3b ), and 4 genes are melanoma/melanocyte marker ( tspan10 , slc45a2 , ptn , 2,8-sialyltranferase ) (Kobayashi et al, 1994; Kuroda et al, 2005; Kang et al, 2007; Zhang et al, 2013; Haltaufderhyde and Oancea 2014; Kimura et al, 2014; Liu et al, 2014; Morice-Picard et al, 2014; Choi et al, 2015; Eaton et al, 2015; Lindsay et al, 2015). The remaining two genes ( CA10 and kirrel3l ) are not well studied and their functions poorly charactrized.…”
Section: Resultsmentioning
confidence: 99%
“…Both Lucifuga species had independently fixed LoF mutations in smtla which is known to increase the number of leucophores at the expense of a reduced number of xanthophores in medaka (Fukamachi, et al 2009). In L. dentata, slc2a11b is pseudogenized and this gene codes for a protein that promotes yellow pigmentation (Kimura, et al 2014; Parichy and Spiewak 2015). Two other genes, trpm1a and trpm1b are also pseudogenized in L. dentata .…”
Section: Discussionmentioning
confidence: 99%